The Correlation of Self-Regulation Theory Constructs and the Incidence of Intradialytic Complications during Hemodialysis - Sandi Alfa Wiga Arsa; Miftah Chairunnisa (STIKes Patria Husada Blitar, 2021)
Hemodialysis is currently applied as a routine treatment that is widely used by patients with chronic kidney failure, though complications still occur during dialysis. Self-regulation is a kind of theoretical model that represents the effect of perceived disease on behavior and health-related consequences. There is a process of problem representation, coping and appraisal or assessment of coping success involved in self-regulation. This study aimed to determine the correlation between self-regulation theory constructs and the incidence of intradialytic complications during hemodialysis. This was a descriptive analytic study with cross-sectional design. Consecutive sampling resulted in 42 respondents. Logistic regression results obtained disease representation variable with timeline (p=0.122; OR=0.412) and control (p=0.068; OR=0.582) sub-variables; as well as coping variable with Problem-focused (p=0.219; OR=0.912) and emotion-focused (p=0.036; OR=0.3) sub-variables. Intradialytic complications are complex conditions that involve many factors, but the patient's psychological adaptation process also deserves to be considered in developing self-regulation among hemodialysis patients. It is necessary to consider the provision of health education based on the constructs of this self-regulation theory, especially on variables/factors that have a correlation with the incidence of intradialytic complications in order to improve self-management among hemodialysis patients to get a better life.